Estudo cefalométrico-radiográfico das alterações dento-esqueléticas em pacientes com má oclusão de Classe III submetidos a tratamento ortodôntico-cirúrgico - Basilio, Leticia Modesto (2005)
The purpose of this cephalometric study was to evaluate, by lateral cephalograms, the dento-skeletal alterations of Class III patients submitted to orthodontic-surgical treatment. The experimental sample comprised of 16 male and female Brazilian patients and average presurgical age of 21 years and 11 months, with Class III malocclusion requiring mandibular setback surgical treatment. Cephalograms were taken for each patient at initial phase, presurgical phase and postsurgical phase, which had been compared to cephalograms of natural normal occlusion s control group. According to applied methodology and the evaluation of the results, by statistical analysis, Class III patients requiring mandibular setback surgery were characterized by a bad relationship between skeletal bases, represented by a good position of the maxilla and mandibular prognathism, increased lower anterior face height, lingual inclination of mandibular incisors and symphysis and labial inclination on maxillary incisors. At the end of presurgical orthodontic treatment, clockwise mandibular rotation, lingual inclination and extrusion of maxillary incisors, labial inclination of mandibular incisors and cortical plate remodeling of the symphysis was observed. Class III patients at presurgical phase had acquired dental alveolar characteristics similar to normal occlusions. The behavior of upward and backward repositioning of mandibular dental and skeletal structures caused by orthognathic surgery, provided a balance of these structures, in relation to normal occlusion.